2016
DOI: 10.3390/ma9110888
|View full text |Cite
|
Sign up to set email alerts
|

Do Dental Resin Composites Accumulate More Oral Biofilms and Plaque than Amalgam and Glass Ionomer Materials?

Abstract: A long-time drawback of dental composites is that they accumulate more biofilms and plaques than amalgam and glass ionomer restorative materials. It would be highly desirable to develop a new composite with reduced biofilm growth, while avoiding the non-esthetics of amalgam and low strength of glass ionomer. The objectives of this study were to: (1) develop a protein-repellent composite with reduced biofilms matching amalgam and glass ionomer for the first time; and (2) investigate their protein adsorption, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 56 publications
1
17
0
10
Order By: Relevance
“…[1][2][3][4][5][6] However, studies showed that resin composites had thicker biolm formation and higher secondary caries incidence, compared to other restorative materials such as amalgams and glass ionomer cements. [7][8][9] Secondary (recurrent) caries adjacent to the restoration margins was reported as one of the most frequent causes of restoration failures. 1,[9][10][11] Therefore, it would be highly desirable to develop a new generation of therapeutic composites with antibacterial and remineralization capabilities to tackle secondary caries.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, studies showed that resin composites had thicker biolm formation and higher secondary caries incidence, compared to other restorative materials such as amalgams and glass ionomer cements. [7][8][9] Secondary (recurrent) caries adjacent to the restoration margins was reported as one of the most frequent causes of restoration failures. 1,[9][10][11] Therefore, it would be highly desirable to develop a new generation of therapeutic composites with antibacterial and remineralization capabilities to tackle secondary caries.…”
Section: Introductionmentioning
confidence: 99%
“…A rugosidade resultante da degradação pelos ácidos pode favorecer o acúmulo de biofilme na superfície rugosa, inflamação gengival se próximo ao tecido gengival, a predisposição à cárie secundária se houver a formação de gaps na interface resina/dente, bem como, o manchamento do material pela deposição de pigmentos ou descoloração da resina (Zhang et al, 2016).…”
Section: Erosãounclassified
“…Características inerentes aos materiais restauradores também tem influência na deposição do biofilme e na consequente degradação do material (Wang et al, 2014). A rugosidade, topografia, conteúdo de carga, hidrofobicidade e composição dos monômeros metacrilatos (Beyth et al, 2007;Beyth et al, 2008;Zhang et al,2016) permitem a adesão das proteínas salivares e a colonização das bactérias cariogênicas, como o S. Mutans (Nedejkovic et al, 2017). A presença desse biofilme cariogênico nos materiais restauradores aumentam ainda mais a rugosidade e predispõem a estrutura dental ao desenvolvimento de cárie secundária, ou formação de novas lesões de cárie na interface dente-restauração, tornando um ciclo que irá levar à falha das restaurações (Gregson et al, 2012;Zhang et al, 2017).…”
Section: Adesão De Biofilmeunclassified
See 2 more Smart Citations